2005
DOI: 10.1164/rccm.200502-259oc
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Obstructive Pulmonary Disease in Korea

Abstract: Seventeen percent of Korean adults over the age of 45 years have mild chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
121
3
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 30 publications
13
121
3
5
Order By: Relevance
“…Because women are less likely to smoke than men in most countries, the prevalence of COPD is usually higher in men than women (7,8,23,24). In a study performed in Elazığ-Turkey, the prevalence of cigarette smoking was higher in men (58.7%) than in women (13.1%) (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because women are less likely to smoke than men in most countries, the prevalence of COPD is usually higher in men than women (7,8,23,24). In a study performed in Elazığ-Turkey, the prevalence of cigarette smoking was higher in men (58.7%) than in women (13.1%) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Population-based surveys using spirometry have shown that the disease is often under-diagnosed in the US, Japan, Korea, Spain, Sweden, and South America (4,(6)(7)(8)(9)(10). There is a large difference among national COPD prevalence estimates depending on self-reported diagnoses (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not possible to differentiate asthma and COPD in an individual over 40 years old by spirometry alone (34)(35)(36), although the use of the post-bronchodilator spirometry value is supposed to reduce the false-positive cases. However, the spirometry criterion adopted in our study is the one most commonly described in the COPD documents (9,10) and used in epidemiological studies (37)(38)(39) and allows us to compare our results to those of O.A. Nascimento et al…”
Section: Discussionmentioning
confidence: 99%
“…Although cases enrolled in these analyses were confirmed using HRCT, the gold standard for diagnosing bronchiectasis (Ooi et al 2002), only patients with severe bronchiectasis requiring medical evaluation or health care utilization were enrolled as cases; those with asymptomatic or mild symptoms may not have been evaluated using HRCT, resulting in undetected bronchiectasis cases and underestimation of the prevalence of bronchiectasis. A growing body of evidence shows that the true prevalence of chronic respiratory diseases such as COPD, when evaluated using objective diagnostic methods, is much higher than prevalence estimated by reported or physician-diagnosed cases (Kim et al 2005). To overcome this limitation in previous studies, and estimate the true prevalence of bronchiectasis, the same diagnostic method should be performed in all study populations.…”
Section: Respiratory Symptoms % (N)mentioning
confidence: 99%